Effect of Aloe Vera Gel (Aloe Vera) on Accelerating Miliaria Healing in Infants (0-12 Months) - Agustina, Lusinta; Andriyani, Asti (Mandalika Institute, 2024)
One of the skin diseases that often affects babies and toddlers is miliariasis or prickly heat. According to the World Health Organization (WHO, 2016) reported that of 80% of miliariasis sufferers per year, 65% of them occur in infants and toddlers. Miliariasis or prickly heat or often called sweat is a skin disorder caused by the closure of skin pores so that sweat cannot come out. Especially because the atmosphere around the baby is very warm or humid. Miliaria is common on the forehead, neck, parts of the body covered with clothing (chest and back), as well as places that often experience pressure or friction of clothing. Aloe vera can be used as an alternative medicine to help the healing process of miliariasis and wounds due to prickly heat. To determine the effect of giving aloe vera gel (Aloe Vera) on the acceleration of miliaria healing in infants (0-12 months). The design of this study is quasi-experimental with sampling using a non-probability sampling method with a purposive sampling technique. The research was conducted at the Edelweiss Mom and Baby Aesthetic Care Center from February 2024 to October 2024. The population in this study is children aged 0-12 months with miliaria with samples based on inclusion and exclusion criteria. A sample of 32 babies was divided into 2 groups, each of which was 16 babies with miliaria who were given aloe vera gel (Aloe Vera) topically and 16 other babies who were not given aloe vera gel (Aloe Vera). The statistical test used univariate analysis and bivariate analysis with α = 0.05. The results of this study showed that as many as 32 babies were divided into two groups: an experimental group given aloe vera gel and a control group without treatment. The results showed significant improvement in the treatment group, with 68.8% of the babies experiencing a reduction in itching. The control group showed no significant changes. Wilcoxon and Mann-Whitney's statistical tests proved that aloe vera gel accelerates the healing of miliaria in babies. The application of aloe vera gel has been proven to be effective in accelerating the healing of miliaria in babies aged 0-12 months. Aloe vera gel can be a safe and effective alternative to natural therapy in overcoming skin problems in babies, especially miliaria. This study supports the use of aloe vera gel as part of infant skin care, with significant results in improving the condition of miliaria.